The Impact of Marriage with a Large Age Difference on Household Harmony from an Islamic Legal Perspective (Case Study in Blang Bladeh Village, Jeumpa District, Bireuen Regency) - Ismunandar; Savinatun Naja (International Journal of Sharia Studies, 2024)
The large age difference between husband and wife tends to cause many differences that will make it difficult for couples to unite thoughts and opinions. This is a challenge in the household to be able to make the household intact and harmonious. Therefore, the author wants to research this matter with two problem formulations, namely how the Islamic law reviews marriages with large age differences in household harmony and how the impact of marriages with large age differences on household harmony in Blang Bladeh Village, Jeumpa District, Bireuen Regency. In this study, the author uses a type of field research (Field Research) with a qualitative approach and uses descriptive methods. The data sources are primary data in the form of interviews with researchers in Blang Bladeh Village, Jeumpa District, Bireuen Regency, and also secondary data, namely books, books and research results that are relevant to the title of this research. Based on the results of the author's research, the author can conclude that in Islamic law there is no prohibition on marriage with a large age gap between husband and wife. And household harmony is not influenced by the age factor of the couple who are far apart. The impact of marriage with a large age difference on household harmony in Blang Bladeh Village, Jeumpa District, Bireuen Regency is to cause two positive and negative impacts, namely the emergence of a sense of mutual respect and understanding of each other and becoming more patient as well as the existence of differences in perspective, differences in communication styles and decision making.